ECOLOGICAL EDUCATION OF FUTURE SOCIAL WORKERS AS A COMPONENT OF THE ETHICAL PARADIGM OF SOCIAL WORK - Balashova, Natalia (Personality and environmental issues, 2026)
The article examines the transformation of ethical standards in social work in the context of contemporary socio-ecological challenges, global crises, and digitalization. Special attention is given to integrating the ecological dimension into the professional activities of social workers, which involves combining the principles of social justice and ecological responsibility. The concepts of "green social work" and ecological social work are considered interdisciplinary approaches aimed at ensuring equal access to a safe environment, protecting natural resources, and improving the quality of life of the population. International standards and practices are analyzed, including the Global Social Work Program and the philosophy of "Buen Vivir," which emphasize the harmonious coexistence of humans, communities, and nature, as well as the need to foster ecological awareness among citizens. The article outlines the main tasks of the modern social worker as an ecological agent of change: supporting vulnerable population groups, implementing environmental programs and projects, protecting the right to a safe environment, and promoting sustainable behavior patterns. The preparation of future social workers is examined through the integration of ecological education and transformative learning, which contributes to the development of critical thinking, professional sensitivity, ethical reflection, systems thinking, and competencies required to work effectively in risk-prone situations. The study results confirm the importance of forming a new professional identity for social workers capable of effectively combining humanistic values with sustainable development principles. The article emphasizes that the ecological dimension of professional practice and education is a key factor in ensuring social and ecological justice in contemporary society and in fostering resilient communities.